How Energy Supports Our Brain to Yield Consciousness: Insights From Neuroimaging Based on the Neuroenergetics Hypothesis - Chen, Yali; Zhang, Jun (Frontiers in Systems Neuroscience, 2021)
Consciousness is considered a result of specific neuronal processes and mechanisms in the brain. Various suggested neuronal mechanisms have been laid forth, including the information integration theory, global neuronal work space, and neuronal construction of time and space as in the context of the temporo-spatial theory of consciousness. However, despite their focus on different neuronal mechanisms, these theories neglect the energetic-metabolic basis of the neuronal mechanisms that supposedly yield consciousness. Based on findings in physiological (sleep), pharmacological (general anesthesia) and pathological (vegetative state/unresponsive wakeful syndrome)-induced loss of consciousness in both human subjects and animals, we here suggest that energetic-metabolic processes focusing on adenosine-triphosphate, glucose, and γ-aminobutyrate/glutamate are indispensable for normal brain networks functional connectivity that renders consciousness possible. Therefore, we speak of energetic-metabolic predispositions of consciousness that complement current theories focused on the neural correlates of consciousness.